Aging in India: problem and potentialities - Bose, A. B. (ed.); Gangrade, K D(ed.) (New Delhi, 1988)
The aging of populations is taking place in both developed and developing countries due to the lowering of birth rates and death rates andincreased life expectancy.
Keywords: Aging